VENTILATOR ASSOCIATED PNEUMONIA AMONG PATIENTS ON MECHANICAL VENTILATION AT TERTIARY CARE CENTRES: Ventilator Associated Pneumonia - Rafiq, Dr Muhammad Yasir; Ikram, Aamer; Afzal, Amna; Zaman, Gohar; Usman, Bushra; Ayyub, Muhammad (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency of ventilator associated pneumonia (VAP) among patients on mechanical ventilation, and to identify the causative bacterial pathogens and antibiotic susceptibility pattern of isolated microorganisms in intensive care units of tertiary care settings. Study Design: Descriptive cross sectional. Place and Duration of Study: This study was conducted at Microbiology Department, Armed Forces Institute of Pathology (AFIP), Rawalpindi, from Dec 2014 to Aug 2015. Material and Methods: A total of 176 patients on mechanical ventilation were included in the study; patients having respiratory tract infection before putting on ventilator were excluded. Endotracheal aspirate (ETA) and Bronchoalveolar lavage (BAL) samples were collected aseptically from patients on mechanical ventilation on day zero i.e. the day on which the patient was put on ventilator to rule out any previous respiratory tract infection and then after 48 hours to observe the development of VAP. Samples were processed in the laboratory by standard culture techniques, pathogens were identified and their antibiotic susceptibility was performed as per CLSI guidelines. Results: Out of 176 patients on mechanical ventilation, 59 (33.5%) developed VAP. Acinetobacter baumanii being the predominant pathogen isolated from 32 (54.2%) patients followed by MRSA 11 (18.6%), Klebsiella pneumoniae 9 (15.2%), Pseudomonas aeruginosa 5 (8.47%) and Stenotrophomonas maltophila from 2 (3.38%) patients. Conclusion: Frequency of VAP is quite high in our setup, identification of causative bacterial pathogens and their antibiotic susceptibility pattern will not only help in providing effective treatment to the patients but will also help in the formulation of antibiogram according to local resistance patterns for empirical therapy and to reduce the morbidity and mortality.